2018
DOI: 10.1371/journal.pone.0203901
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Family Focused Mental Health Practice Questionnaire in measuring home visitors’ family focused practice

Abstract: BackgroundWorldwide maternal mental illness poses a major public health issue. Supporting maternal mental health and family health is a core aspect of home visiting. Increasingly the benefits of family focused treatments to maternal mental illness are being recognised. However, there are few reliable and valid measures that attempt to assess this type of practice.ObjectivesTo explore the psychometric properties of the Family Focused Mental Health Practice Questionnaire in a population of home visitors.MethodsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
1
16
1
Order By: Relevance
“…A strength is that the Family-Focused Mental Health Questionnaire has been used in other countries, which creates the ability to compare outcome differences, although some caution should be exercised in comparing concepts across countries [90]. Only 10 of the 17 subscales had high enough reliability to be further analysed in this study [78], which contributes to knowledge on the weaknesses of some subscales [33, 56, 75, 91] and provides useful information on refining the measure.…”
Section: Discussionmentioning
confidence: 99%
“…A strength is that the Family-Focused Mental Health Questionnaire has been used in other countries, which creates the ability to compare outcome differences, although some caution should be exercised in comparing concepts across countries [90]. Only 10 of the 17 subscales had high enough reliability to be further analysed in this study [78], which contributes to knowledge on the weaknesses of some subscales [33, 56, 75, 91] and provides useful information on refining the measure.…”
Section: Discussionmentioning
confidence: 99%
“…While Maybery et al () established the content and construct validity of the FFMHPQ in Australia, subsequent studies have found varying degrees of reliability in the scale inferring inconsistencies when used across disciplines, services and countries (Grant et al, , ; Laletas, Goodyear, & Reupert, ; Lauritzen & Reedtz, ; Tungpunkom et al, ). Consequently, an exploratory factor analysis (EFA) was conducted to determine scale validity in the current population of health visitors (Leonard, Linden, & Grant, ). The EFA revealed a two‐factor solution, consisting of 20 items.…”
Section: The Studymentioning
confidence: 99%
“…Family-focused practice (FFP) is a term used to describe mental health care that addresses the needs of both the parent with the illness and their children and other family members (Leonard et al , 2018; Ward et al , 2017). It is a broad concept encompassing an overarching approach to mental health care, inclusion of family members in care, and a range of specific interventions (Leonard et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Family-focused practice (FFP) is a term used to describe mental health care that addresses the needs of both the parent with the illness and their children and other family members (Leonard et al , 2018; Ward et al , 2017). It is a broad concept encompassing an overarching approach to mental health care, inclusion of family members in care, and a range of specific interventions (Leonard et al , 2018). Benefits of FFP for children include improved communication about, and understanding of, the parent’s mental illness, increased family cohesion (Compas et al , 2011; Siegenthaler et al , 2012) and a positive influence on psychosocial development (Cooklin, 2013).…”
Section: Introductionmentioning
confidence: 99%